Environmental Sustainability in Maritime Infrastructures - Esteban, María Dolores; López-Gutiérrez, José-Santos; Negro Valdecantos, Vicente; Ortega, José Marcos (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue is entitled "Environmental Sustainability in Maritime Infrastructures". Oceans and coastal areas are essential in our lives from several different points of view: social, economic, and health. Given the importance of these areas for human life, not only for the present but also for the future, it is necessary to plan future infrastructures, and maintain and adapt to the changes the existing ones. All of this taking into account the sustainability of our planet. A very significant percentage of the world's population lives permanently or enjoys their vacation periods in coastal zones, which makes them very sensitive areas, with a very high economic value and as a focus of adverse effects on public health and ecosystems. Therefore, it is considered very relevant and of great interest to launch this Special Issue to cover any aspects related to the vulnerability of coastal systems and their inhabitants (water pollution, coastal flooding, climate change, overpopulation, urban planning, waste water, plastics at sea, effects on ecosystems, etc.), as well as the use of ocean resources (fisheries, energy, tourism areas, etc.).